Chinese and Indian Public Pension Systems and Universal Old-age Security in Times of Rapid Demographic Changes - Silvan Siefert (Contemporary Chinese Political Economy and Strategic Relations: An International Journal, 2018)
India and China have become countries of rapid economic growth and at the same time of socio-economic contrast. The classical old-age security arrangement has focused mainly on the formal sector and excluded a majority of the population working in the informal sector. Consequently, along the road of economic growth, increasing living standards and higher wages, a good proportion of the population are threatened by old-age poverty. Elderly people in rural areas, people in precarious employment situations, such as migrant workers, disabled and sick people belong to the high risk-group of people at risk of old-age poverty due to the lack of old-age security arrangements for these groups in the informal sector. In times of rapidly aging societies and growing socioeconomic disparity, New Delhi and Beijing have realized the increasing importance and urgency of extending pension coverage to all parts of society. In recent years decision-makers in both countries have made huge efforts to reform their pension systems and to alleviate poverty among the elderly today and in coming years. The political commitment is closely linked to the demand for output legitimacy to gain public support from these groups. Contrary to the theoretical imperative of the superiority of democracies, China seems to be doing much better than India in the provision of universal coverage for the informal sector. To answer the puzzle, this article examines the impact of institutional features and socio-economic characteristics on the pension policy process. It is argued that country-specific institutional settings and political commitments affect the learning ability in the policy making process, which determines the output performance of pension politics and the realization of universal coverage for old-age security in the informal sector.